'Canadian Charter of Rights and Freedoms': The challenge of the individual and collective rights of Aboriginal people - Isaac, Thomas (WINDSOR YEARBOOK OF ACCESS TO JUSTICE, 2002)
Section 25 of the 'Canadian Charter of Rights and Freedoms' is an important, yet not fully understood, interpretive provision. This section plays an important role in Canada's constitutional framework by shielding the rights of aboriginal people from negative impacts that the 'Charter' may have on such rights. However, the exact scope and significance of the role that section 25 plays in 'Charter' interpretation is uncertain. Through a textual analysis of section 25, this paper attempts to provide guidance on the provision's possible interpretation and application. In particular, the implementation of section 25 and the maintenance of a balance between the individual and collective rights of aboriginal people will be explored Such commentary is required because the role of section 25 will inevitably become more relevant as more aboriginal self-government agreements and arrangements are concluded.